Changes in core temperature during an elite female rugby sevens tournament - Henderson, M. J.; Chrismas, B. C. R.; Stevens, C. J.; Coutts, A. J.; Taylor, L. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To characterize player core temperature (Tc) across a World Rugby Women`s Sevens Series tournament day (WRWSS) and determine the efficacy of commonly employed cold-water-immersion (CWI) protocols. Methods: Tc was measured in 12 elite female rugby sevens athletes across 3 games (G1-3) from day 1 of the Sydney WRWSS tournament. Symptoms of exertional heat illness, perceptual scales, CWI details, playing minutes, external-load data (measured by global positioning systems), and wet-bulb globe temperature (range 18.5°C-20.1°C) were also collected. Linear mixed models and magnitude-based inferences were used to assess differences in Tc between periods (G1-3 and warm-ups [WU]). Results: Average Tc was "very likely" lower (effect size; ±90% confidence limit -0.33; ±0.18) in G1 than in G2. Peak Tc was "very likely" (0.71; ±0.28) associated with increased playing time. CWI did not remove the accumulated Tc due to WU and match-play activity (~1°C-2°C rise in Tc still present compared with Tc at WU onset for players =6-min match play). Conclusions: Elite WRWSS athletes experienced high Tc during WU (Tc peak 37.9-39.0°C) and matches (Tc peak 37.9-39.8°C), a magnitude known to reduce intermittent high-intensity physical performance (=39°C). The CWI protocol resulted in players (=6-min match play) with ~1°C to 2°C raised Tc compared with Tc at WU onset.